Articles - Shane R. Gauthier; Katie Black; Sharon Goulet (First Peoples Child & Family Review, 2020)
Family & Community Support Services (FCSS) in Calgary is a joint municipal and provincial funding program. The program is designed to develop, support, and fund preventive social services. FCSS Calgary has a number of benefits and truly makes a difference in the community. At-risk youth and vulnerable senior citizens have avenues for positive community involvement, family violence victims are safer, newcomers are welcomed and can feel at home in Calgary, citizens have access to information about the community and crisis services, and urban Aboriginal people are able to develop leadership skills within the community. FCSS programs and agencies align with at least one of the funding priorities (Strengthening Neighbourhoods and Increasing Social Inclusion, outlined in the Social Sustainability Framework). Increasing Social Inclusion concentrates on five populations: families, children and youth, seniors, immigrants, and Aboriginal people (City of Calgary, Social Sustainability, 2010).The new Social Sustainability Framework helps the community in a number of ways. It guides funding decisions by providing FCSS Calgary with clear and consistent principles. By aligning funded programs with identified objectives and outcomes, it helps FCSS account for and communicate its impact on the community. There is an abundance of statistics that support the need for culturally appropriate programs for urban Aboriginal peoples. Research demonstrates urgency for these programs and the current social landscape of urban Aboriginal children, youth, and families. For example, between 1996 and 2006, the Aboriginal population across Canada grew by 45% to reach close to 1.2 million persons, representing 3.8% of the Canadian population. (Statistics Canada, 2008, Canadian Demographics at a Glance, p. 34).Two examples of urban Aboriginal programs from Metis Calgary Family Services (MCFS) is presented within FCSS’s Sustainability Framework; Native Network, and Little Dancing Buffalo. Key words: At risk youth, vulnerable senior citizens, ...